BIOTECH DRIVES THE WATER PURIFICATION INDUSTRY TOWARDS A CIRCULAR ECONOMY (Academicia Globe: Inderscience Research, 2023)
Rising populations and pollution levels mean that water purification is now more crucial than ever before. However, much of the industry is still using water treatment methods that originated over 100 years ago. “Coming from biotechnology, I’m really surprised about how little innovation we find in the water industry, since it’s the world’s largest natural resource… and it’s the world’s third largest market. Only oil and energy, as far as I know, have a larger revenue number than water treatment. Biotechnological methods of water purification are considered in this article.